Algebra


  1. If x +
    1
    = √3 , then the value of x30 + x24 + x18 + x12 + x6 + 1 is
    x










  1. View Hint View Answer Discuss in Forum

    Using Rule 8,

    x +
    1
    = √3
    x

    On cubing both sides,
    ⇒ x3 +
    1
    + 3x +
    1
    = 3√3
    x3x

    ⇒ x3 +
    1
    + 3√3 = 3√3
    x3

    ⇒ x3 +
    1
    = 0
    x3

    ∴ Expression = x30 + x24 + x18 + x12 + x6 + 1
    Expression = x24( x6 + 1 ) + x12( x6 + 1 ) + 1( x6 + 1 )
    Expression = ( x6 + 1 )( x24 + x12 + 1 )
    Expression = x3x3 +
    1
    ( x24 + x12 + 1 ) = 0
    x3

    Correct Option: D

    Using Rule 8,

    x +
    1
    = √3
    x

    On cubing both sides,
    ⇒ x3 +
    1
    + 3x +
    1
    = 3√3
    x3x

    ⇒ x3 +
    1
    + 3√3 = 3√3
    x3

    ⇒ x3 +
    1
    = 0
    x3

    ∴ Expression = x30 + x24 + x18 + x12 + x6 + 1
    Expression = x24( x6 + 1 ) + x12( x6 + 1 ) + 1( x6 + 1 )
    Expression = ( x6 + 1 )( x24 + x12 + 1 )
    Expression = x3x3 +
    1
    ( x24 + x12 + 1 ) = 0
    x3


  1. If x -
    1
    2 = 3 , then the value of x6 +
    1
    equals
    xx6










  1. View Hint View Answer Discuss in Forum

    x -
    1
    2 = 3
    x

    ⇒ x2 +
    1
    - 2 = 3
    x2

    ⇒ x2 +
    1
    = 3 + 2 = 5
    x2

    On cubing both sides,
    x2 +
    1
    3 = (5)3
    x2

    ⇒ x6 +
    1
    + 3x2 +
    1
    = 125
    x6x2

    ⇒ x6 +
    1
    + 3 × 5 = 125
    x6

    ⇒ x6 +
    1
    = 125 – 15 = 110
    x6

    Correct Option: C

    x -
    1
    2 = 3
    x

    ⇒ x2 +
    1
    - 2 = 3
    x2

    ⇒ x2 +
    1
    = 3 + 2 = 5
    x2

    On cubing both sides,
    x2 +
    1
    3 = (5)3
    x2

    ⇒ x6 +
    1
    + 3x2 +
    1
    = 125
    x6x2

    ⇒ x6 +
    1
    + 3 × 5 = 125
    x6

    ⇒ x6 +
    1
    = 125 – 15 = 110
    x6



  1. If x +
    1
    = 3 , then the value of x5 +
    1
    is :
    xx5










  1. View Hint View Answer Discuss in Forum

    Using Rule 1 and 8,

    x +
    1
    = 3
    x

    On squaring both sides,
    x +
    1
    2 = 9
    x

    ⇒ x2 +
    1
    + 2 = 9
    x2

    ⇒ x2 +
    1
    = 9 – 2 = 7 ... (i)
    x2

    Again,
    x +
    1
    3 = (3)3 = 27
    x

    ⇒ x3 +
    1
    + 3x +
    1
    = 27
    x3x

    ⇒ x3 +
    1
    + 3 × 3 = 27
    x3

    ∴ x3 +
    1
    = 27 - 9 = 18 ...(ii)
    x3

    x2 +
    1
    x3 +
    1
    = 18 × 7 = 126
    x2x3

    ⇒ x5 +
    1
    + x +
    1
    = 126
    x5x

    ⇒ x5 +
    1
    = 126 – 3 = 123
    x5

    Correct Option: D

    Using Rule 1 and 8,

    x +
    1
    = 3
    x

    On squaring both sides,
    x +
    1
    2 = 9
    x

    ⇒ x2 +
    1
    + 2 = 9
    x2

    ⇒ x2 +
    1
    = 9 – 2 = 7 ... (i)
    x2

    Again,
    x +
    1
    3 = (3)3 = 27
    x

    ⇒ x3 +
    1
    + 3x +
    1
    = 27
    x3x

    ⇒ x3 +
    1
    + 3 × 3 = 27
    x3

    ∴ x3 +
    1
    = 27 - 9 = 18 ...(ii)
    x3

    x2 +
    1
    x3 +
    1
    = 18 × 7 = 126
    x2x3

    ⇒ x5 +
    1
    + x +
    1
    = 126
    x5x

    ⇒ x5 +
    1
    = 126 – 3 = 123
    x5


  1. When 2x +
    2
    = 3 , then value of x3 +
    1
    + 2 is
    xx3










  1. View Hint View Answer Discuss in Forum

    2x +
    2
    = 3
    x

    On dividing by 2,
    x +
    1
    =
    3
    x2

    On cubing both sides,
    x +
    1
    3 =
    27
    x8

    ⇒ x3 +
    1
    + 3x +
    1
    =
    27
    x3x8

    ⇒ x3 +
    1
    +
    3 × 3
    =
    27
    x328

    ⇒ x3 +
    1
    =
    27
    -
    9
    x382

    ⇒ x3 +
    1
    =
    27 - 36
    x38

    ⇒ x3 +
    1
    =
    -9
    x38

    ∴ x3 +
    1
    + 2 = 2 -
    9
    =
    16 - 9
    =
    7
    x3888

    Correct Option: B

    2x +
    2
    = 3
    x

    On dividing by 2,
    x +
    1
    =
    3
    x2

    On cubing both sides,
    x +
    1
    3 =
    27
    x8

    ⇒ x3 +
    1
    + 3x +
    1
    =
    27
    x3x8

    ⇒ x3 +
    1
    +
    3 × 3
    =
    27
    x328

    ⇒ x3 +
    1
    =
    27
    -
    9
    x382

    ⇒ x3 +
    1
    =
    27 - 36
    x38

    ⇒ x3 +
    1
    =
    -9
    x38

    ∴ x3 +
    1
    + 2 = 2 -
    9
    =
    16 - 9
    =
    7
    x3888



  1. If x = ³√x2 + 11 - 2 , then the value of (x3 + 5x2 + 12x) is









  1. View Hint View Answer Discuss in Forum

    x = ³√x2 + 11 - 2
    ⇒ x + 2 = ³√x2 + 11
    On cubing both sides,
    (x + 2)3 = x2 + 11
    ⇒ x3 + 23 + 3x2 × 2 + 3x × 22 = x2 + 11
    ⇒ x3 + 8 + 6x2 + 12x = x2 + 11
    ⇒ x3 + 5x2 + 12x = 11 – 8 = 3

    Correct Option: B

    x = ³√x2 + 11 - 2
    ⇒ x + 2 = ³√x2 + 11
    On cubing both sides,
    (x + 2)3 = x2 + 11
    ⇒ x3 + 23 + 3x2 × 2 + 3x × 22 = x2 + 11
    ⇒ x3 + 8 + 6x2 + 12x = x2 + 11
    ⇒ x3 + 5x2 + 12x = 11 – 8 = 3